A global survey of Hypervirulent Aeromonas hydrophila (vAh) identified vAh strains in the lower Mekong River Basin and diverse opportunistic pathogens from farmed fish and other environmental sources - M. Yasin, Ina Salwany; Karim, Muhammad Manjurul; Xu, Tingbi; Figueras, Maria J.; Sayuti, Mohamad Azzam; Mey, Sothea (American Society for Microbiology, 2023)
Hypervirulent Aeromonas hydrophila (vAh) has emerged as the etiologic agent of epidemic outbreaks of motile Aeromonas septicemia (MAS) in high-density aquaculture of farmed carp in China and catfish in the United States, which has caused millions of tons of lost fish. We conducted a global survey to better understand the evolution, geographical distribution, and phylogeny of vAh. Aeromonas isolates were isolated from fish that showed clinical symptoms of MAS, and pure cultures were screened for the ability to utilize myoinositol as the sole carbon source. A total of 113 myo-inositol-utilizing bacterial strains were included in this study, including additional strains obtained from previously published culture collections. Based on a gyrB phylogeny, this collection included 66 A. hydrophila isolates, 48 of which were vAh. This collection also included five new vAh isolates from diseased Pangas catfish (Pangasius pangasius) and striped catfish (Pangasianodon hypophthalmus) obtained in Cambodia and Vietnam, respectively. Genome sequences were generated from representative vAh and non-vAh isolates to evaluate the potential for lateral genetic transfer of the myo-inositol catabolism pathway. Phylogenetic analyses of each of the nine genes required for myo-inositol utilization revealed the close affiliation of vAh strains regardless of geographic origin and suggested lateral genetic transfer of this catabolic pathway from an Enterobacter species. Prediction of virulence factors was conducted to determine differences between vAh and non-vAh strains in terms of virulence and secretion systems. Core genome phylogenetic analyses on vAh isolates and Aeromonas spp. disease isolates (55 in total) were conducted to evaluate the evolutionary relationships among vAh and other Aeromonas sp. isolates, which supported the clonal nature of vAh isolates.